1997
DOI: 10.1136/bmj.315.7115.1045
|View full text |Cite
|
Sign up to set email alerts
|

Association between features of the insulin resistance syndrome and alzheimer's disease independently of apolipoprotein e4 phenotype: cross sectional population based study

Abstract: Objective: To determine the association between features of the insulin resistance syndrome and Alzheimer's disease. Design: Cross sectional population based study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
257
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 403 publications
(285 citation statements)
references
References 29 publications
(27 reference statements)
21
257
0
3
Order By: Relevance
“…Elderly people with diabetes have an especially increased risk of mild cognitive impairment (MCI) [18] and an association of diabetes with MCI varies with amyloid subtype (amnestic) MCI and nonamnestic MCI) and number of domains, and with the sex of the patient, with females being more susceptible than males [19]. Diabetes as a significant risk factor for dementia or AD has been clearly established by studies in the US [20] and several other countries (Taiwan [21], China [22], Japan [23], and Finland [24]). T2D has also been associated with an increased risk of vascular dementia [25], and pre-diabetic insulin resistance is a risk factor for AD pathology and reduced memory function [26].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Elderly people with diabetes have an especially increased risk of mild cognitive impairment (MCI) [18] and an association of diabetes with MCI varies with amyloid subtype (amnestic) MCI and nonamnestic MCI) and number of domains, and with the sex of the patient, with females being more susceptible than males [19]. Diabetes as a significant risk factor for dementia or AD has been clearly established by studies in the US [20] and several other countries (Taiwan [21], China [22], Japan [23], and Finland [24]). T2D has also been associated with an increased risk of vascular dementia [25], and pre-diabetic insulin resistance is a risk factor for AD pathology and reduced memory function [26].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…92 Similar findings have been reported in dementia studies. Hypertension was associated with Alzheimer's disease in subjects 69-78 years 93 and low blood pressure was associated with both Alzheimer's disease and vascular dementia in subjects …”
Section: Hypertension and Cognitive Functionmentioning
confidence: 99%
“…In addition, previous research indicated that higher consumption of tea, which is linked to lower cholesterol level, was proved to take a protective effect on cognition (7), and higher cholesterol was linked to faster cognitive decline among patients with Alzheimer's disease (8). In contrast, other studies provide contradictory findings that demonstrated no association between cholesterol concentrations and cognitive impairment or dementia (9,10), and even that higher concentrations of cholesterol were associated with a decreased risk of cognitive impairment among the elderly (11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the existing studies only focused on the total population (4,5,(8)(9)(10)(11)(12)(13)(14)(15)(16); therefore, there is still some ambiguity with respect to potential differences in the relationships of cognition and lipids in men and women. Although the association between cholesterol and cognitive function is strongly age-dependent (17), yet few of previous studies focused on the oldest old (13).…”
Section: Introductionmentioning
confidence: 99%